A Paradigm Shift in Early Drug Development: Individualizing to More Patient Benefit - Vinall, Phil (MD Conference Express, 2012)
With the increasing the use of biomarkers in cancer treatment, the emphasis on selecting the right treatment for the right patient takes on added significance in early drug development. This article discusses the difficulties inherent in selecting patients for early drug-development studies.